Analysis of the Implementation of Quality Management Systems in Construction Projects central Business Disctric Batavia Pantai Indah Kapuk, Jakarta City - Hendra Hafit; Rifaldi Adi Saputra (Asosiasi Dosen Muda Indonesia, 2025)
This research on a building construction project in the Central Business District (CBD) Batavia PIK Jakarta aims to analyze the implementation of the Quality Management System (QMS) in the project, focusing on identifying the practices of this quality management system, the challenges faced, and its impact on project quality outcomes. The method used in this research is descriptive quantitative with a survey approach. The research results show how the effective implementation of a Quality Management System (QMS) can improve the quality of construction projects, reduce the risk of errors, and increase stakeholder satisfaction. However, challenges exist, such as a lack of understanding of QMS principles among workers and resistance to change from some parties. This research also found that top management involvement and adequate employee training are key factors in the successful implementation of the Quality Management System (QMS). Recommendations include developing continuous training programs and improving communication among all stakeholders to support more effective QMS implementation in the future.